Review on the control of waterborne diseases – The Islamic approach - Md Isa, Muhammad Lokman; Jainul, Mohammed Abdullah; Mat Yusof, Afzan (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Introduction: Scarcity of fresh water is currently blighting the population of the least developed countries around the world. According to WHO, waterborne diseases accounts for 4.1% of total disability adjusted life years (DALYs) with a mortality rate of 1.8 million per year. Numerous pathogens and chemicals may be the potential sources of water contamination that leads to waterborne diseases in humans. Some pathogens are only active and express disease whilst within the host. The aim of this article is to identify the cause of water-borne diseases and how to control it from the Islamic perspective. Material and Methods: In this review we had compiled the latest scientific findings related to waterborne diseases and integrated them with Islamic approach of cleanliness. There are many Hadiths of the Prophet (peace be upon him) (PBUH) regarding methods of cleanliness with scientific background to control waterborne diseases. Water pollution may be a natural process, men made, intentional or accidental. More often than not, man are infected after accidently consuming or coming in contact with contaminated water Results: Scientific literature search reveals that individual hygiene and sanitation is the most prominent way to prevent waterborne diseases. In Islam, Prophet Muhammad (PBUH) puts a great emphasize on purification in terms of personal cleanliness and made it mandatory to follow rule to remain pure both physically and spiritually. Conclusions: Sunnatic approaches of cleanliness may hinder waterborne disease.